The impact of maritime trade liberalization and economic integration to Malaysia - Zul Kepli, Mohd Yazid (Transstellar Journal Publications and Research Consultancy Private Limited (TJPRC), 2016)
Malaysian maritime trade sector is very much liberalized with 80 percent of Malaysian goods and cargoes being shipped to Malaysia using foreign ships. With regional liberalization of trade and services being top on ASEAN agenda, steps are being taken to further liberalize trade and services sectors. This article explores the maritime logistic industry in Malaysia and analyzes how the liberalization of maritime trade, and now, ASEAN economic integration, impacts on the conduct, structure and performance of its maritime trade sector. The benefits of regional liberalization of trade must be balanced with effective policies and meticulous implementation to protect the interest of all parties: foreign and domestic. Unmonitored and unregulated liberalization will be harmful to both society and economy.